INSTAGRAM AND ITS ROLE AS A SOCIAL ENTERPRISE TRANSPARENCY MEDIA IN INDONESIA - Wijayanti, Anita; Narsa, I Made; Hamidah, Hamidah (Universitas PGRI Madiun, 2023)
ABSTRACTThis study identifies the role of Instagram as a medium of transparency for three Social Enterprises that operate in the creative sector with empowering women as part of their social mission. This study employs content analysis with the help of NVivo software on various narratives, photos, and videos uploaded through the Instagram account from January to May 2023. The researcher also interviewed the CEO and beneficiaries via Instagram live chat. This study indicates the significant role of Instagram in building trust and media dialogue between companies and the public, which are essential in achieving company accountability, legitimacy, and sustainability.ABSTRAKStudi ini mengidentifikasi peran Instagram sebagai media transparansi bagi tiga Usaha Sosial yang bergerak di sektor kreatif dengan pemberdayaan perempuan sebagai bagian dari misi sosial mereka. Penelitian ini menggunakan analisis konten dengan bantuan software NVivo pada berbagai narasi, foto, dan video yang diunggah melalui akun Instagram pada bulan Januari hingga Mei 2023. Peneliti juga mewawancarai CEO dan penerima manfaat melalui live chat Instagram. Studi ini menunjukkan peran penting Instagram dalam membangun kepercayaan dan dialog media antara perusahaan dan publik, yang penting dalam mencapai akuntabilitas, legitimasi, dan keberlanjutan perusahaan.